ASVAC2019: 7th Asian Vaccine Conference. Issue 7 (2nd July 2020) - Linn, Kyaw; Bravo, Lulu; Goh, Daniel Yam Thiam; Nelson, E. Anthony S.
ABSTRACT: The 7th Asian Vaccine Conference (ASVAC 2019) was held in Yangon, Myanmar from 13 to 15, September 2019. It brought together stakeholders in the field of vaccination to address challenges and issues relevant to clinical practice and immunization programs in the region. The conference themed " Immunization: sustaining health security in Asia ", included pre-conference workshops, a Vaccinology Masterclass, plenary lectures, symposia, and poster presentations. There were over 700 participants ~ 400 local and 300 international from 31 countries ~ and 55 international and local speakers from 19 countries. An Asian EPI managers' meeting was also held on 11–12 September in Naypyidaw, the new capital of Myanmar, and was hosted by the Ministry of Health and Sports, Myanmar with support from World Health Organization, UNICEF and other partners. This inter-regional meeting aimed to strengthen the cooperation and collaboration of EPI Managers and others involved in implementing immunization programs in the region. The conference was organized by the Immunization Partners in Asia Pacific (IPAP) and hosted by Myanmar Pediatric Society and the Ministry of Health and Sports, Myanmar. Other partners included the Confederation of Meningitis Organization, Philippine Foundation of Vaccination, Pediatric Infection Disease Society of the Philippines, Asia Pacific Alliance for the Control of Influenza, PATH, ROTA Council, International Society of Tropical Pediatrics, Asian Society for Pediatric Infection Diseases and other partners. Previous conferences have been held in Siem Reap (2009), Manila (2010), Jakarta (2011), Cebu (2013), Hanoi (2015) and Singapore (2017). The 8th Asian Vaccine Conference will be held in Penang, Malaysia in 2021 to further IPAP's vision of a world where no one suffers from a vaccine-preventable disease.